Treatment of Pediatric Colchicine Poisoning with Single-Pass Albumin Dialysis: A Case Report - Atessa Bahadori; Rishil Patel; Cal Robinson; Steve Balgobin; Michael Zappitelli; Nithiakishna Selvathesan (Case Reports in Nephrology and Dialysis)
Introduction: Colchicine has a narrow therapeutic index, and doses >0.5 mg/kg are considered toxic with a high mortality rate. Case Presentation: A previously healthy 15-year-old presents to the emergency department with abdominal pain and vomiting following intentional ingestion of colchicine (0.56 mg/kg) 12 h prior. By 24 h post-ingestion, they developed a multi-organ injury with hepatic dysfunction, coagulopathy, lactic acidemia, and pancytopenia, which prompted consideration of extracorporeal therapy (ECT). Considering the characteristics of colchicine, they were treated with continuous venovenous hemodiafiltration (CVVHDF) with single-pass albumin dialysis (SPAD) for 42 h. They were subsequently discharged from the intensive care unit 48 h after stopping CVVHDF with normal kidney function, resolved coagulopathy, and resolving pancytopenia and hepatic dysfunction. The rationale for CVVHDF with SPAD was based on the high protein binding, variably high volume of distribution, previous reports showing a sieving coefficient of 0.2 with CVVH, and the high mortality risk. We anticipated a high potential for rebound. Thus, continuous clearance would facilitate redistribution from the extravascular to intravascular space. SPAD was used to enhance the elimination of protein-bound fractions; the principle is that adding albumin to dialysate creates a protein-binding disequilibrium where the drug from the blood side may bind to albumin on the dialysate side. Conclusion: Colchicine ingestion of >0.5 mg/kg is highly toxic, and in addition to supportive management, continuous kidney replacement therapy with SPAD may be considered.